Exploring Project-Based Learning in English for Tourism Course: Enhancing Students Engagement and Practical Communication Skills - Nehe, Berita Mambarasi; Rahman, Zainatul Shuhaida Abdull (PROJECT (Professional Journal of English Education), 2025)
This study explores the implementation of Project-Based Learning (PjBL) in an English for Tourism course to enhance student engagement and develop practical communication skills. In the context of the tourism industry, effective communication in English is essential for success. Therefore, this research focuses on how PBL, a student-centered learning approach, can improve learners' abilities to communicate in real-world tourism scenarios. Weekly projects were assigned to university students, requiring them to work in groups and present tourism-related topics, such as cultural heritage, tour packages, promoting tourist destinations, and hospitality services. The study utilized qualitative methods, including classroom observations and student interviews, and analysis of project presentations, to evaluate the impact of PjBL on their language proficiency and engagement. Findings reveal that PjBL significantly increased students’ engagement and practical communication skills. Participation, promoted collaborative learning, and enhanced their practical use of tourism-specific English. Furthermore, students demonstrated improved confidence in public speaking and better application of communication strategies adjusted to the tourism. The research concludes that PjBL is an effective learning model for bridging theoretical learning with practical, industry-relevant skills in English for Tourism courses.